2014
DOI: 10.1038/bcj.2014.56
|View full text |Cite
|
Sign up to set email alerts
|

Percentage of urinary albumin excretion and serum-free light-chain reduction are important determinants of renal response in myeloma patients with moderate to severe renal impairment

Abstract: Reversal of renal dysfunction significantly affects the prognosis of multiple myeloma (MM) with renal impairment (RI). There is no reliable test for predicting reversibility of RI in MM patients. We postulated that MM with high albuminuria may reflect glomerular disease that is difficult to reverse. Here, we examined the impact of urinary albumin excretion. We retrospectively analyzed 279 patients admitted to our hospital from April 2000 to December 2013. Clinical variables and laboratory data that may affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
5
2
Order By: Relevance
“…Explanatory variables: age, 46–48,60,61,6371,74,77,80 serum LDH level, 46,51,62,64,65,73,76,7981,88 light chains level, 44,4654 β 2 microglobulin level, 51,62,64,70,71,7981,89,90 albumin level, 53,6466,71,79,80 M protein level, 59,70,9193 t(14), 55–59 pain, 69,83,85,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Explanatory variables: age, 46–48,60,61,6371,74,77,80 serum LDH level, 46,51,62,64,65,73,76,7981,88 light chains level, 44,4654 β 2 microglobulin level, 51,62,64,70,71,7981,89,90 albumin level, 53,6466,71,79,80 M protein level, 59,70,9193 t(14), 55–59 pain, 69,83,85,…”
Section: Resultsmentioning
confidence: 99%
“…Numbers in brackets are the number of attributes in each group. In total, 56 MM attributes were identified as significant, that is, those that have a significant relationship with another attribute; these were grouped into five categories: disease characteristics, 4454 cytogenetic factors, 55–59 patient characteristics, 45–48,51,53,55,6081 QoL, 69,75,82,83 and symptoms. 46,69,71,8287 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11,19 In relation to these results, we previously reported that the percentage of urinary albumin excreted reflects the pathogenesis of RI and predicted renal response in myeloma patients. 20 However, some patients continue to develop severe RI, despite novel anti-myeloma therapy and the achievement of early FLC reduction. In patients receiving novel agents, an additional factor, which can indicate the reversibility of RI, remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Hutchison et al [13] in their study on 39 patients with biopsy proven myeloma kidney, had found a linear relationship between FLC reduction and renal recovery, with a 60% reduction in FLC by day 21 being associated with renal recovery for 80% of the population. A retrospective analysis of 279 patients by Sugihara et al [14] have found that reduction of iFLC 95% at day 21 (P = 0.015) and urinary albumin ≦ 25% (P = 0.007) was significant for any renal response in patients with myeloma kidney. In our study, we found that 84% reduction in iFLC value was associated with renal recovery with a sensitivity and specificity of 77.7% and 75% respectively.…”
Section: Discussionmentioning
confidence: 99%